Industrial Training Institute, Mohali, Punjab - Sharma, Rajeev, (SAGE Knowledge. Cases., 2017)
Mr. R.P. Singh was appointed as the new principal at the Industrial Training Institute in Mohali, Punjab in 2006. Part of the building was incomplete and several other parts were unfurnished, and maintenance was poor. Space in front of the building, meant for a lawn and a garden, was barren. There was no structured system for placement of students and faculty and staff were disinterested in their job. In a period of four years, Mr. Singh turned things around. For promoting excellence in Industrial training Institutes across the country. Enhanced involvement of employees, improved infrastructure, efficient and timely utilisation of funds and additional resources put the institute on a sound footing. The case describes how Mr. Singh changed things for the better.